Perilaku Investasi sebagai penerapan gaya hidup halal masyarakat Indonesia: tinjauan Theory of Planned Behavior - Mega Noerman Ningtyas; Dyah Febriantina Istiqomah (Jurnal Ekonomi Modernisasi, 2021)
The survey shows that the community's ability to utilize Islamic financial products is still low. This fact contradicts the potential development of a halal lifestyle and the increasing number of middle-class Muslims, and the fact that 87.2% of Indonesians are Muslim. It turns out that not many people know and take advantage of Islamic financial products, including Islamic investment. The purpose of the study was to determine the factors behind investment behaviour in sharia instruments as a form of implementing the halal lifestyle of people in Indonesia. The research subjects are Muslims who have or are currently investing in sharia securities, with 100 respondents. Data were collected by distributing online questionnaires. The data analysis technique uses Partial Least Square. The results show that attitudes and perceived behavioural control affect intention in investing in sharia securities, while subjective norms do not affect. Investment intention in sharia securities affects investment decisions. This study proves that investors' assessments and perceptions of factors that can support their investment activities, such as knowledge and skills, can influence their interest in investing in the Islamic capital market. Thus, it is essential to conduct training for novice investors to provide exposure to the Islamic capital market.